Profitability and profit efficiency of certified groundnut seed and conventional groundnut production in Northern Ghana: A comparative analysis - Dominic Tasila Konja; Franklin N. Mabe; Richard Oteng-Frimpong (Cogent Economics & Finance, 2019)
This study seeks to compare profitability and profit efficiency of certified groundnut seed (CGS) and conventional groundnut (CG) production in Northern Ghana using cross-sectional data. The two-step stochastic metafrontier profit model was used to estimate profit efficiencies and their determining factors for CGS and CG producers. The study found that CGS production is more profitable and profit efficient than CG production. Whilst profit efficiency of CGS is influenced by age, education, extension visits, Farmer-Based Organisation meetings, and farming experience, profit efficiency of CG producers is influenced by educational status, access to extension, and access to mobile phone. To increase profit and profit efficiency, the capacity of CGS producers should be built to incentivise them to upscale CGS production so as to bridge the demand deficit in the country. Also, farmers should be trained to enter into CGS production.
Keywords: 330; Profit efficiency; two-step stochastic metafrontier profit model; certified groundnut seed and conventional groundnut